Patterns of consumer movements in west Thessaly - Bennison, David J. (The Greek Review of Social Research, 1980)
The structure of the settlement system of West Thessaly has been shown to consist of a well-defined four-level hierarchy, with the most important places being the two nomos seats of Trikala and Kardhitsa, and below them six smaller urban centres. This paper examines the extent to which the structure is reflected in the functioning of the system as revealed by patterns of consumer movements. Using information collected by circulating questionnaires in the region via the secondary schools, the patterns of movement for thirteen goods and services are described. Differences in the average distances travelled for different goods and services were found, reflecting the differential use made of the four levels of the hierarchy by consumers. The provision of goods down to relatively low levels of the settlement hierarchy in Greece means that intensive use is made of small urban settlements for the purchase of many consumer durables. Only for the highest order functions do Trikala and Kardhitsa dominate within the region, and for these large centres outside West Thessaly (especially Larissa, Athens and Thessaloniki), exert an influence. After considering briefly the theoretical aspects of these findings, the paper concludes with an assessment of their implications for town and regional planning.